PDA (Prolonged Depolarizing Afterpotential)-Defective Mutants: The Story of nina's and ina's-pinta and santa maria, Too. - Pak, W.L.; Shino, S.; Leung, H.T. (Journal of Neurogenetics, 2012)
Our objective is to present a comprehensive view of the PDA (prolonged depolarizing afterpotential)-defective Drosophila mutants, nina's and ina's, from the discussion of the PDA and the PDA-based mutant screening strategy to summaries of the knowledge gained through the studies of mutants generated using the strategy. The PDA is a component of the light-evoked photoreceptor potential that is generated when a substantial fraction of rhodopsin is photoconverted to its active form, metarhodopsin. The PDA-based mutant screening strategy was adopted to enhance the efficiency and efficacy of ERG (electroretinogram)-based screening for identifying phototransduction-defective mutants. Using this strategy, two classes of PDA-defective mutants were identified and isolated, nina and ina, each comprising multiple complementation groups. The nina mutants are characterized by allele-dependent reduction in the major rhodopsin, Rh1, whereas the ina mutants display defects in some aspects of functions related to the transduction channel, TRP (transient receptor potential). The signaling proteins that have been identified and elucidated through the studies of nina mutants include the Drosophila opsin protein (NINAE), the chaperone protein for nascent opsin (NINAA), and the multifunctional protein, NINAC, required in multiple steps of the Drosophila phototransduction cascade. Also identified by the nina mutants are some of the key enzymes involved in the biogenesis of the rhodopsin chromophore. As for the ina mutants, they led to the discovery of the scaffold protein, INAD, responsible for the nucleation of the supramolecular signaling complex. Also identified by the ina mutants is one of the key members of the signaling complex, INAC (ePKC), and two other proteins that are likely to be important, though their roles in the signaling cascade have not yet been fully elucidated. In most of these cases, the protein identified is the first member of its class to be so recognized.